The Criticism of Ideology in the Miraculous Narrative Text: A Comparative Study of Marquez and Fadhel Al-Azawi's Selected Novels - Hussein, Khalid; Al-Dbow, Aysar (Dirasat: Human and Social Sciences, 2020)
Novelists turned to wonder as an actual practitioner in modern narrative writings to criticize the tragic reality, Wonders has emerged from the womb of suffering, and the bereaved statements of the creators who were silenced by the whips of darkness and intellectual oppression devices, So, I employed this wonder as a critical means in the novel achievement, it is an anthem for the concerns of reality and try to criticize and express it, Between the boredom of tradition and the tendency to renew, the wonder came really creative, adventurous and amazing, To recount the imagined superhero as a documenting history, and to mix two directions that combine a dialectic relationship: magic and reality, she took from the narrative achievement a field for her because of the wide space it holds to accommodate the ideas and visions that she advocated for. And distributed by role to the imagined characters and events and times in the content of these works, so some of the selected models were Gabriel García Márquez and Fadel Azzawi narrative appointed for research by a comparative analytical study. They have a tarweed relationship that has been spread over areas of the world of Dystopia in its various forms, unjustly suppressing and muzzling the mouths.